Perception on the Traditional Korean Medicine According to the Existence of a Chronic Disease - Kim, Jihye (J Pharmacopuncture, 2020)
OBJECTIVES: Chronic diseases (CDs) continue to increase due to advances in medicine and increase in lifespan, affecting quality of life and resulting in economic loss through treatment costs. This study addressed the perception characteristics of the effectiveness of Korean medicine (KM) based on the existence of a CD to determine the national preference for KM treatment. METHODS: Using data from the 2017 National Survey of KM Usage, we evaluated the perception on treatment effect of 16 diseases by dividing them into the CD group and the non-CD group. Response reliability was verified by applying the chi-square test (χ(2)-test) analysis method of the Statistical Package for the Social Sciences (SPSS) statistical program. RESULTS: The analysis of the perception on effectiveness of KM for patients with CD (n = 1,050, 21.0%) and for patients with non-CD (n = 3,950, 79.0%) showed an overall similar trend for all the 16 diseases. The response rates of having some treatment effect were high for nine diseases namely, disc-related disease (CD 70.7%, non-CD 73.1%), osteoarthritis (CD 72.3%, non-CD 72.4%), frozen shoulder and shoulder pain (CD 79.6%, non-CD 81.4%), back pain (CD 84.6%, non-CD 85.0%), sprain (CD 84.8%, non-CD 84.1%), facial nerve paralysis (CD 73.5%, non-CD 71.7%), stroke (CD 66.2%, non-CD 62.8%), digestive disease (CD 53.3%, non-CD 50.0%), and common cold and rhinitis (CD 44.7%, non-CD 44.8%). CONCLUSION: The present results found that there was little difference in the perception on effectiveness of KM for each of the 16 diseases in patients with CD and non-CD, however, 70% or more of the respondents recognized some treatment effect on musculoskeletal disorders, regardless of the existence of CD. Preferential political support for KM treatment of chronic musculoskeletal disorders is recommended.